Masyarakat Ideal dalam Al-Mujtama’ Al-Mitsali Kama Tunazhzhimuhu Suratu An-Nisaa’ Karya Syaikh Muhammad Al-Madani - Muhammad Rabbany Tarman, Al-Faiz; Andini Suparmun, Arifah Cahyo; Angga Zakariya, Aulif (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
The problem of objectification ultimately becomes a debate when discussing the principles of the ideal society. The focus is on discussing the conception of the ideal society according to Sheikh Muhammad Al-Madani in the book Al-Mujtama' Al-Mitsali Kama Tunazhzhimuhu Suratu An-Nisaa' which has been translated into Ideal Society in the Perspective of Surah AnNisaa'. To elaborate on this conception, the author uses the theory of objectification of science according to Kuntowijoyo. Objectification refers to Kuntowijoyo's term in the book Islam as Science. For Al-Madani, each letter in the Qur'an has special characteristics. Al-Madani describes the Qur'an as a book of guidance in which there are letters that have distinctive characteristics in encouraging the heart and soul. The Qur'an is a source that has its own analogies, examples, principles and is independent in the perspective he takes in Surah AnNisa. Surah An-Nisa guarantees that the Islamic social order is ideal, as reflected in the principles and guidelines underlying its formation, the expectations that develop within it, and the laws that it enforces. These important principles are first, equality among people; second, faith and obedience to the shari'a of Allah Swt.; third, justice in law, the implementation of court decisions, and testimony; fourth, social security. Al-Madani's conception of the ideal society in the perspective of surah An-Nisa offers the most prominent among the four points above is the equality between men and women, namely the equality of women's social functions with men. The argument offered by al-Madani is An-Nisa (4): 124. Objectification of science is science and believers for all human beings, not only for believers. As for the conception of the ideal society according to AlMadani, the four points mentioned above are the objectification of science and act as religious control in the context of a society.